Multi-objective optimization of ship resistance and seakeeping using an improved Voronoi-based parallel sequential sampling method - Dongqin Li; Yu Zhang; Yanqing Yin; Wenwen Chen; Bohan Wang; Zishuai Wang; Lingfeng Lu (Ocean Engineering, 2026)

Granular hydrogel gradient microenvironments drive functional osteochondral interface regeneration - Jing Wang; Wenbo Zhong; Chengxiang Sha; Yu Shen; Zhaowei Yin; Lingfeng Yuan; Bin Liang; Xi Zeng; Jing Zhang; Ziyi Yu (Chemical Engineering Journal, 2026)

A 1D spectral approach for efficient modal identification of thin-walled members in shell finite element models - Yiling Dai; Shaokuai Wang; Mingming Xiang; Lingfeng Yin; Zhanjie Li (Engineering Structures, 2025)

Survival and physiological responses of pearl oyster Pinctada maxima seedlings: Comparative analysis of wet (submerged) and dry (waterless) transportation methods - Xing Zheng; Ze Yin; Lingfeng Wang; Shangkun Wei; Meng Zhang; Xinfei Shao; Hebert Ely Vasquez; Zhifeng Gu (Aquaculture, 2025)

Strength and behavior of axially and eccentrically loaded built-up closed sections using four cold-formed steel open sections - Lingfeng Yin; Shaokuai Wang; Yongbiao Wang; Tianyang Deng; Zhanjie Li (Engineering Structures, 2024)

Nanofiltration membrane with modified nano-gradient structure and positive charge for Li separation from high Mg/Li ratio brine - Peng Zhao; Fei Guo; Lingfeng Wang; Huange Zhen; Ning Zhang; Shaohua Yin; Guoli Zhou; Xuehua Ruan; Gaohong He; Xiaobin Jiang (Desalination, 2024)

Exposure, bioaccumulation, and risk assessment of organophosphate flame retardants in crayfish in the middle and lower reaches of the Yangtze River - Qiuhong Peng; Lingfeng Peng; Jin Liu; Yan Liu; Xin Liu; Jiaojiao Yin; Shuo Duan; Xiaofang Liu; Yuzhi Li; Zhiyong Gong; Qiao Wang (Science of The Total Environment, 2024)

Stable oganocopper(III) complexes generated via oxidative addition - Lingfeng Yin; Wei Liu (Science Bulletin, 2024)

Revisiting the East Asian summer monsoon structure: a combined effect of condensational heating and synoptic eddy activities - Shengjie Chen; Xiu-Qun Yang; Jiabei Fang; Linyuan Sun; Lingfeng Tao; Xiaozhuo Sang; Manman Yin (Climate Dynamics, 2023)

Solvent effect to modulate nitrogen dopant in Co-N-C catalysts for oxygen reduction reaction acceleration - Lingfeng Li; Guokang Han; Yandi Wen; Yuxin Liu; Rang Xiao; Wei Zhang; Fanpeng Kong; Lei Du; Yulin Ma; Pengjian Zuo; Chunyu Du; Geping Yin (Fuel, 2023)

Transcriptome Analysis of Reciprocal Hybrids Between Crassostrea gigas and C. angulata Reveals the Potential Mechanisms Underlying Thermo-Resistant Heterosis - Gaowei Jiang; Yin Li; Geng Cheng; Kunyin Jiang; Jianmin Zhou; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

Niche overlap and divergence times support niche conservatism in eastern Asia–eastern North America disjunct plants - Xue Yin; Scott Jarvie; Wen‐Yong Guo; Tao Deng; Lingfeng Mao; Minhua Zhang; Chengjin Chu; Hong Qian; Jens‐Christian Svenning; Fangliang He (Global Ecology and Biogeography, 2021)
Aim The plant species sharing ancestors now disjunctly distributed in eastern Asia (EAS) and eastern North America (ENA) have long been a biogeographic puzzle. Species within the EAS–ENA disjunct genera are presumed to exhibit niche conservatism, the tendency of closely related species to be more ecologically similar, reflecting lineages’ common evolutionary history. However, the hypothesis has not been well examined at the species level. Location EAS and ENA. Time period Current. Major taxa studied Species within the EAS–ENA disjunct genera. Methods We compiled data on climate, species occurrence, growth form, and phylogeny to examine niche conservatism. We first built a phylogenetic tree to select intercontinental congeneric pairwise species and obtained their divergence times. We then quantified the observed niche overlaps with Schoener’s D , which has a 0–1 range, based on species occurrence and climate of species’ native ranges. To obtain projected distributions, each species’ niche was projected to the non‐native region using ensemble ecological niche models. Projected‐related niche overlaps were then calculated using projected distributions and the corresponding climatic conditions. Results Average observed niche overlaps of congeneric pairwise species were relatively small: .124, .211 and .109 for all, herbaceous and woody species, respectively. Both observed and projected‐related niche overlaps had significant negative relationships with divergence times of intercontinental congeneric pairwise species, with niche overlap for herbaceous species being higher than that for woody plants when controlling for divergence times. Main conclusions We conclude that the significant negative relationships between niche overlap and divergence times of congeneric pairwise species confirm niche conservatism among species of EAS–ENA disjunct plants and that the extent of niche conservatism is slightly different for herbaceous and woody plants. These findings suggest the potential role of allopatric speciation in EAS, and could help to understand the evolutionary history and the Asian‐bias diversity pattern of the EAS–ENA disjunct plants.

Effects of climate and topography on the diversity anomaly of plants disjunctly distributed in eastern Asia and eastern North America - Xue Yin; Hong Qian; Xinghua Sui; Minhua Zhang; Lingfeng Mao; Jens‐Christian Svenning; Robert E. Ricklefs; Fangliang He (Global Ecology and Biogeography, 2021)
Aim Differences in physiography have been proposed to explain the diversity anomaly for vascular plants between environmentally similar regions of eastern Asia (EAS) and eastern North America (ENA). Here, we use plant species within disjunct genera to examine whether differences in topography contribute to the diversity anomaly and whether the richness–environment relationships differ between regions. Disjunct plants are used to ensure that the diversity anomaly relates to post‐disjunction evolution and diversification rather than regional differences in clade ages or immigration. Location EAS and ENA. Time period Current. Major taxa studied Plant taxa disjunctly distributed in EAS and ENA. Methods We compiled county‐level plant distribution data, and calculated species richness and variables of topography and climate within unit grid cells. We compared estimated coefficients of region effects among models, where richness was fitted with or without topography and climate. Topography and climate were also used to separately model within‐region spatial diversity patterns using spatial simultaneous autoregressive error models. Results The coefficients of region effects varied from −.776 for the model only including region to −.309 when topography was controlled for, but remained significant. Climate dominated the spatial diversity patterns in ENA. In contrast, the influence of climate (14.2%) on species richness was weaker than that of topography (18.3%) in the warm area of EAS. Relations to elevation and temperature varied between regions, shifting between positive and negative relationships in several cases. Main conclusions Our results demonstrate that variability in local topography contributes to the strong regional anomaly in plant species richness between EAS and ENA. Nevertheless, the diversity anomaly persists after controlling for local topography and climate. EAS and ENA also exhibit contrasting richness–environment relationships, providing another divergent aspect between the EAS–ENA disjunct floras. Our findings highlight that regional differences in topography or other environmental factors may underlie the diversity anomaly.

Regional disparity in extinction risk: Comparison of disjunct plant genera between eastern Asia and eastern North America - Houjuan Song; Alejandro Ordonez; Jens‐Christian Svenning; Hong Qian; Xue Yin; Lingfeng Mao; Tao Deng; Jian Zhang (Global Change Biology, 2021)
Climate and land cover changes are increasing threats to biodiversity globally. However, potentially varying biotic sensitivity is a major source of uncertainty for translating environmental changes to extinction risks. To reduce this uncertainty, we assessed how extinction risks will be affected by future human‐driven environmental changes, focusing on 554 species from 52 disjunct plant genera between eastern Asia (EAS) and eastern North America (ENA) to control for differences in environmental sensitivity at the genus level. Species distribution models were used to estimate and compare the vulnerability of species in disjunct genera between the two regions under two climate and land cover change scenarios (RCP2.6 and RCP8.5) in the 2070s, allowing to assess the effects of differences in climate and land cover pressures. Compared with ENA, stronger pressures from climate and land cover changes along with smaller range sizes in EAS translate into a larger number and proportion of species in disjunct genera becoming threatened by the 2070s. These regional differences are more pronounced under a best‐case climate scenario (RCP2.6), illustrating that strong climate change (RCP8.5) may override any regional buffer capacities. The main variables determining extinction risks differed between the two continental regions, with annual temperature range and cropland expansion being important in EAS, and annual precipitation being important in ENA. These results suggest that disparities in regional exposure to anthropogenic environmental changes may cause congeneric species with relatively similar sensitivity to have different future risks of extinction. Moreover, the findings highlight the context‐specific nature of anthropogenic effects on biodiversity and the importance of making region‐specific policies for conservation and restoration in response to the intensifying global changes.

QSAR modeling and in silico design of small-molecule inhibitors targeting the interaction between E3 ligase VHL and HIF-1 $$α $$ α - Jing Pan; Yanmin Zhang; Ting Ran; Anyang Xu; Xin Qiao; Lingfeng Yin; Weineng Zhou; Lu Zhu; Junnan Zhao; Tao Lu; Yadong Chen; Yulei Jiang (Molecular Diversity, 2017)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)